(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article analyzes the role of language clichés in structuring the information fragments of reality and the conceptualization of information in the modern media discourse. The language of media communication is conceptualized in the context of global cliché, because due to the multi-vector information scope, the world is losing its national borders and has no restrictions in time and space. The life of the modern information society is characterized by the accelerated pace of developing systems and mass communications, the technocratic approach to improving the means of producing and distributing the information, applying new information technologies. The diversity of organizing the forms of the world information space, the ways of information flows, the state of the information environment, the mechanisms and methods of distributing misinformation and the hybrid information wars, the development of global and national information security problems give rise to new stereotyped products that have their own discursive representation. Linguistic forms of information processes accordingly create the media image of modern reality and the information world view. Templates, standardization, and clichés are the characteristics of the modern national media discourse. Language clichés act as the constructs of the media space. Performing a regulatory function, such linguistic units structure the national language information world view and produce the mass-media image of the Ukrainian society. The interpretation of real events with the presentation of template fact-comments creates the fragments of the media world view, transforming the means of clichéd structures with information flows into ideological stereotypes.